Mendorong Pertumbuhan UMKM Desa Grujugan Kidul Melalui Strategi Digital Marketing Efektif - Muhammad Putrajaya; Agus Afandi (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2025)
This study empowers MSMEs in Grujugan Kidul Village through digital marketing strategies using the Asset-Based Community Development (ABCD) approach. Activities included training in Google My Business, business legality, and halal certification. The program significantly enhanced participants’ skills, enabling market expansion, increased sales, and improved customer engagement. Despite limited time, the initiative equipped MSMEs to sustain digital practices independently. The findings highlight digital marketing's role in rural business growth and stress the need for extended support and stakeholder collaboration to ensure inclusivity and sustainability. This serves as a reference for developing MSMEs in underserved regions.